Postpartum depression – a mood disorder after delivery - Siedlecka, Dagna; Wróbel-Knybel, Paulina; Krzewicka-Romaniuk, Ewa; Micał, Wojciech; Skoczyński, Marcin (Journal of Education, Health and Sport, 2019)
Postpartum depression (PPD) is a mood disorder characterized by depressive episode symptoms within three months after delivery, lasting between two and six months. The characteristic symptoms of postpartum depression are: exaggerated worry about the child's state of health, which does not cause any concern, weakened bond with the child, obsessive thoughts about harming the child (egodystonic thoughts), egosyntonic, non-obsessive thoughts about killing the child. All psychotropic medications are secreted in breast milk. Pharmacological treatment of PPD is not contraindication for breastfeeding. PPD should be treated because it disturbs formation of a proper bond between mother and child, which has an adverse effect on the child's psychosocial development.